Digital hermeneutics: scaled readings of online depression discourses. Issue 3 (14th October 2021) - van de Ven, Inge; van Nuenen, Tom
Abstract : When it comes to understanding experiences of illness, humanities and social sciences research have traditionally reserved a prominent role for narrative. Yet, depression has characteristics that withstand the form of traditional narratives, such as a lack of desire and an impotence to act. How can a 'datafied' approach to online forms of depression writing pose a valuable addition to existing narrative approaches in health humanities? In this article, we analyse lay people's depression discourses online. Our approach, 'digital hermeneutics', is inspired by Gadamer's dialogical hermeneutics. It consists of a 'scaled reading' on five different scales: platform hermeneutics; contextual reading with term frequency—inverse document frequency (TF–IDF); distant reading with natural language processing topic modelling; hyper-reading with concordance views and close reading. Our corpus consisted of three data sets, from the blogs and message boards of, respectively, time-to-change.org.uk, a UK-based social organisation and movement that aims to counter mental health discrimination and alleviate social isolation by spreading awareness; Sane.org.uk, a leading UK mental health charity that seeks to help people in facing the challenges of mental illness and to improve quality of life; and the subreddit 'r/depression' on web discussion platform reddit. We found that the manner in which people express experiences of illness online is very much dependent on the specific affordances of platforms. We found degrees of 'narrativity' to be correlated to authorship and identity markers: the less 'anonymous' the writing, generally speaking, the more conventionally 'narrative' it was. Pseudonimity was related to more intimate and singular forms, with less pressure to conform to socially accepted and positive narratives of the 'restitution' type. We also found that interactive affordances of the platforms were used to a limited extent, nuancing assumptions about the polyvocality of online depression writing. We conclude by making a claim for increased cooperation between digital and medical humanities that might lead to a field of 'Digital Medical Humanities'.